Resistance of Nineteen Major Caladium Commercial Cultivars to Pythium Root Rot - Zhanao Deng; Brent K. Harbaugh; Richard O. Kelly; Teresa Seijo; Robert J. McGovern (EDIS)
Caladiums (Caladium xhortulanum) are popular ornamental plants widely grown for their bright colorful leaves. Pythium root rot, caused by P. myriotylum, is one of the few soil-borne diseases in caladium that can dramatically reduce plant growth, aesthetic value, and tuber yield. Identification and use of disease-resistant cultivars has proven to be an important and economically viable strategy for integrated management of major diseases in crops and for reducing the use of pesticides. This strategy will be particularly useful for caladiums in the landscape and home gardens, because in such cases choices of root rot control measures are limited. However, information on the resistance level of commercial caladium cultivars has been lacking. This document is ENH996, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date December 2, 2004.